Honey bee pathology - Bailey, Leslie (Academic Press, 1991)
Since the publication of the first edition of this book in 1982, investigation into the pathology of honey bees has progressed considerably. Furthermore, several different agents of disease, some newly discovered, have been causing increasing concern in recent years in many parts of the world. The book contains separate chapters on viruses, bacteria, fungi, protozoa, mites, nematode and insect parasites, non-infectious diseases, and the treatment of diseases. The contents are a thorough revision of the previous edition and incorporate much new information, especially with respect to viruses, ba.